2021
DOI: 10.1007/s40436-020-00336-9
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, analysis, and optimization of dimensional accuracy of FDM-fabricated parts using definitive screening design and deep learning feedforward artificial neural network

Abstract: Additive manufacturing (AM) technologies such as fused deposition modeling (FDM) rely on the quality of manufactured products and the process capability. Currently, the dimensional accuracy and stability of any AM process is essential for ensuring that customer specifications are satisfied at the highest standard, and variations are controlled without significantly affecting the functioning of processes, machines, and product structures. This study aims to investigate the effects of FDM fabrication conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Research studies by O.A.Mohamed et al [4] have been performed regarding the ability of artificial neural networks to predict dimensional characteristics of parts obtained through the FDM process by analysing parameters such as slice thickness, the number of perimeters, deposition angle, part print direction, and raster to raster air-gap. The study compared the precision of neural networks to classic regression techniques and showed that neural networks can account for dimensional deviations.…”
Section: State Of the Artmentioning
confidence: 99%
“…Research studies by O.A.Mohamed et al [4] have been performed regarding the ability of artificial neural networks to predict dimensional characteristics of parts obtained through the FDM process by analysing parameters such as slice thickness, the number of perimeters, deposition angle, part print direction, and raster to raster air-gap. The study compared the precision of neural networks to classic regression techniques and showed that neural networks can account for dimensional deviations.…”
Section: State Of the Artmentioning
confidence: 99%
“…AG can also influence the defects listed: Geometrical accuracy, Porosity, and Surface Roughness. [ 12 , 21 , 22 , 44 , 86 , 110 , 119 , 56 ] [ 22 , 45 , 46 , 120 ] Raster angle (RA) The angle between deposited adjacent strands with respect to the X axis. RA can also influence the defects listed: Geometrical accuracy and Surface Roughness.…”
Section: Printing Parameters and Their Impactmentioning
confidence: 99%
“…RA can also influence the defects listed: Geometrical accuracy and Surface Roughness. [ 21 , 44 , 60 , 88 , 119 , 120 , 121 ], [ 12 , 22 , 45 , 46 , 56 , 66 , 70 , 78 , 104 , 110 ] Road width (RW) Also known as raster width, the width of a deposited stand, which is a function of the extruder nozzle diameter and toolpath parameters. RW can also influence the defects listed: Geometrical accuracy and Surface Roughness.…”
Section: Printing Parameters and Their Impactmentioning
confidence: 99%
“…Definitive screening design (DSD), a three-level fractional factorial design, has been developed recently [32]. It performed better than other traditional experimental designs, such as full factorial design and response surface methodology (RSM), in estimating the main effect, interaction, and quadratic effect [33,34]. Compared to traditional methods, it reduces the experimental runs and, therefore, reduces experimentation time and cost.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammad et al [35] successfully modeled the effect of various fused deposition modeling (FDM) process parameters on the creep and recovery behavior of 3D printed parts using DSD. In another study [33], they modeled and optimized the dimensional accuracy of FDM parts using DSD and deep learning. Luzanin et al [36] investigated the effect of build parameters of FDM on the flexural force of FDM manufactured parts.…”
Section: Introductionmentioning
confidence: 99%